2019
DOI: 10.1016/j.laa.2018.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry of Birkhoff–James orthogonality of operators defined between infinite dimensional Banach spaces

Abstract: We study left symmetric bounded linear operators in the sense of Birkhoff-James orthogonality defined between infinite dimensional Banach spaces. We prove that a bounded linear operator defined between two strictly convex Banach spaces is left symmetric if and only if it is zero operator when the domain space is reflexive and Kadets-Klee. We exhibit a non-zero left symmetric operator when the spaces are not strictly convex. We also study right symmetric bounded linear operators between infinite dimensional Ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…where H is a complex Hilbert space. Since then, many results on local symmetry of Birkhoff orthogonality have been published, especially, in the fields of Banach (or Hilbert) space operators; see [11,13,21,26] for results on spaces of bounded linear operators between Banach spaces, and [3,7,12,[22][23][24][25]27,28] for important techniques about Birkhoff orthogonality in such spaces. See also [18][19][20] for developments in the setting of operator algebras.…”
Section: Introductionmentioning
confidence: 99%
“…where H is a complex Hilbert space. Since then, many results on local symmetry of Birkhoff orthogonality have been published, especially, in the fields of Banach (or Hilbert) space operators; see [11,13,21,26] for results on spaces of bounded linear operators between Banach spaces, and [3,7,12,[22][23][24][25]27,28] for important techniques about Birkhoff orthogonality in such spaces. See also [18][19][20] for developments in the setting of operator algebras.…”
Section: Introductionmentioning
confidence: 99%
“…We now characterize the local symmetry of Birkhoff-James orthogonality in ℓ p . Now, Proposition 2.1 of [14] states that in a smooth, strictly convex space, a point is left-symmetric if and only if it is right-symmetric. Hence the necessity of the right-symmetric case follows from the left-symmetric case.…”
Section: There Existmentioning
confidence: 99%
“…So the extreme points of D[0, 1] in B(H) are precisely those operators which are of unit norm and are also right symmetric. There is also a concept of a left symmetric operator, the study of which can be found in [30,71,79,96].…”
Section: Orthogonality and Geometry Of Normed Spacesmentioning
confidence: 99%